Code reading : the open source perspective - Spinellis, Diomidis (Effective software development series., 2003)
If you are a programmer, you need this book. You've got a day to add a new feature in a 34,000-line program: Where do you start? Page 333 How can you understand and simplify an inscrutable piece of code? Page 39 Where do you start when disentangling a complicated build process? Page 167 How do you comprehend code that appears to be doing five things in parallel? Page 132 You may read code because you have to--to fix it, inspect it, or improve it. You may read code the way an engineer examines a machine--to discover what makes it tick. Or you may read code because you are scavenging--looking for material to reuse. Code-reading requires its own set of skills, and the ability to determine which technique you use when is crucial. In this indispensable book, Diomidis Spinellis uses more than 600 real-world examples to show you how to identify good (and bad) code: how to read it, what to look for, and how to use this knowledge to improve your own code. Fact: If you make a habit of reading good code, you will write better code yourself. 0201799405B02032003.